Decomposing socioeconomic inequalities in alcohol use by men living in South African urban informal settlements - Nozuko Lawana; Frederik Booysen (BMC, 2018)
Abstract Background The prevalence of alcohol consumption among males living in urban settlements in South Africa is high. This paper aims to measure socioeconomic inequalities in alcohol use among men residing in informal settlements and also to examine the factors associated with inequality in alcohol use among men living in informal settlements. Methods The study uses data from the 2016 Study of South African Informal Settlements. Multiple correspondence analysis is used to calculate a wealth index as a measure of socioeconomic status. The Erreygers concentration index is employed to quantify the degree of socioeconomic inequality in alcohol use and decomposition analysis is conducted to assess the factors associated with inequality in alcohol use by men of various age groups. Results There is a socioeconomic-related inequality in alcohol use in informal settlements that discriminates against poor men. Inequality is especially pronounced in the case of males aged 15-34 years and males aged 35-44 years. Wealth status makes the biggest contribution to socioeconomic inequality in alcohol use. The contribution of social determinants of health like marital status and employment status differ across age groups. Employment status contribute more to the alcohol use inequality among males aged 15-34 years while marital status contribute more to the alcohol use inequality among males aged 35-44 years. Being single substantially increases inequality in alcohol use. Conclusion Inequality in alcohol use exists among both younger and older males and discriminate against the poor. Public policies aimed at promoting public health and the prevention of unhealthy behaviours should target younger and middle-aged men from socioeconomically disadvantaged groups. We also suggest policies that target single males in informal settlements.